Guidelines for Accounting Melaka Mobile Units Greenhouse Gas (GHG) Emissions - F. Fam, S; D. Prastyo, D; Yanto, H; L. Maukar, A; A.Jaafar, A; H. Mustaffa, M (International Journal of Engineering & Technology, 2018)
Having a clear picture of greenhouse gas (GHG) emission is essential to understand the spatial emission status and make international comparisons. This study gave an overview on how GHG from the mobile units was measured to produce a pioneer report for Melaka. Global Protocols for Community-Scale Greenhouse Gas Emission (GPC), harmonized emission analysis tool plus (HEAT+) and greenhouse gas (GHG) emission inventory were utilized to produce the mobile unitsâ€™ energy profile and carbon emission in Melaka. Data was collected from federal government agencies and private sectors. The results showed that on-road transportations contributed to the largest GHG (99.51%), followed by railway (0.38%) and lastly aviation (0.03%). Melaka has embarked on a path towards green city by the year 2020 and has to reach the target of reducing carbon emissions up to 40% by the year 2020. These findings are important to assist the local government to define mitigation programs and refine policies to enhance liveability in Melaka by having low carbon resident in future.Â Â